Neutral axis modeling and effectiveness of functionally graded piezoelectric energy harvesters. (1st April 2019) - Larkin, K.; Abdelkefi, A.
Abstract: The reduced-order modeling and performance of single-layered functionally graded piezoelectric energy harvesting systems are investigated. The choice of single-layered functionally graded materials gives the opportunity to minimize the volume of the energy harvesting system and hence increases its power density. Also, the unique composition of a functionally graded material allows for the creation of durable piezoelectric energy harvesters. As for the modeling of functionally graded piezoelectric materials, there has been some debate due to the location of the neutral axis compared to the central axis of the system. To this end, the use of the geometric central axis as the neutral axis to approximate the behavior of single-layered functionally graded cantilever piezoelectric energy harvesters and the possibility of getting erroneous predictions are explored. The effects of the material distribution and the scaling of the energy harvesting system form macro- to nano-scale are also considered. It is proved that the use of the central axis model can lead to significant inaccuracies in the estimation of the natural frequencies of the energy harvester for certain material distributions. Additionally, the central axis approximation exhibits a reduced coupling between the electrical circuit and the beam structure which could result in inefficient design of the energy harvester. It is also shown that the percentage of the metallic material can significantly affect both the natural frequencies and the power density of the system. The obtained results show the importance of considering the neutral axis modeling for efficient and optimal design of functionally graded piezoelectric energy harvesters.